“Let the State Decide It All for Me”: The Role of Migration and Integration Policy in the Decision-Making of Ukrainian Refugee Women in Germany - Valeria Lazarenko (Journal of International Migration and Integration, 2024)
Abstract While German migration policies aim to provide temporary protection and integrate Ukrainian refugees into German society as early as possible, the procedures and ideas of integration might be perceived differently by the beneficiaries. The feeling of “permanent temporariness” has been persistent among Ukrainians since March 2022. In this situation, some of the refugees renounce their agency and put responsibility on decision-making onto the state, while others oppose the idea of “being integrated” since they see their time in Germany as temporary, and their future in Ukraine as soon as the security situation allows them to return. Drawing on the experiences of single Ukrainian women who received protection in Germany, the paper presents an anthropological perspective on person–state interactions in the context of refugees' future-planning. How do German policies for supporting Ukrainian refugees impact their “stay or return” decision-making? Do the policies address their needs now and allow them to make investments for the future, or, on the contrary, contribute to their decision to return to Ukraine, which appears to be “simpler” and “more predictable”? How does the experience of going through bureaucratic procedures contribute to the sense of having agency and being capable of shaping their today and tomorrow? To answer these questions, I am going to present the reasonings and emotions concerning bureaucratic procedures that are closely intertwined with the planning of their future by Ukrainian refugees in Germany.
Keywords: 330; Ukrainian refugees; Integration; Bureaucracy; Agency; Temporariness